2020
DOI: 10.1021/acscatal.0c03594
|View full text |Cite
|
Sign up to set email alerts
|

A Whole-Cell Inorganic-Biohybrid System Integrated by Reduced Graphene Oxide for Boosting Solar Hydrogen Production

Abstract: The photoelectron transfer between semiconductors and cells is the rate-determining step that controls the solar H2 production of whole-cell inorganic-biohybrid systems (IBSs). Herein, we constructed an IBS by using reduced graphene oxide (RGO) to integrate Shewanella oneidensis MR-1 (SW) cells and Cu2O, which exhibited a 11–38-fold enhancement of photocatalytic H2 production compared with RGO-free IBSs (Cu2O/SW and Cu2O/organic electron mediator/SW). Further analysis revealed that RGO provided multifunctional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 60 publications
(81 reference statements)
1
74
0
Order By: Relevance
“…This finding was consistent with the previous reported Cu 2 O/RGO/Shewanella oneidensis system. [31] Overall, these results suggested that the electron transfer pathway at the interface of I-HTCC and E. coli cells was established and played an important role for the photo-enhanced H 2 production in the biohybrid system.…”
Section: H 2 Production Performance and The Role Of Photoelectronsmentioning
confidence: 67%
See 4 more Smart Citations
“…This finding was consistent with the previous reported Cu 2 O/RGO/Shewanella oneidensis system. [31] Overall, these results suggested that the electron transfer pathway at the interface of I-HTCC and E. coli cells was established and played an important role for the photo-enhanced H 2 production in the biohybrid system.…”
Section: H 2 Production Performance and The Role Of Photoelectronsmentioning
confidence: 67%
“…As those shown in Figure 2b, the H 2 production was only slightly increased with the simple mixing of I-HTCC and untreated E. coli cells, which was caused by the random electrons diffusion across cell membrane. [31] Therefore, increasing in H 2 production of I-HTCC@E. coli biohybrid system indicated that the close interfacial interactions between I-HTCC and E. coli was essential for the electrons delivery. To confirm the role of photoelectrons in H 2 production, the scavenger study was performed with the supplement of Cr (VI), a strong oxidant, in the biohybrid system.…”
Section: H 2 Production Performance and The Role Of Photoelectronsmentioning
confidence: 99%
See 3 more Smart Citations